Miniaturization of terahertz spectroscopy - Lum, Ying Hong (Nanyang Technological University, 2023)
The use of terahertz waves in medical research has gained attention in recent years due to the non-ionizing energy levels and non-destructive properties. Despite having promising capabilities comparable to existing medical spectroscopy and imaging techniques, the technology remains confined to research settings primarily due to challenges associated with generating and detecting terahertz waves.